Effect of β-casein A2 cow milk supplementation on physical growth, inflammation, growth-related hormones, and nutritional biomarkers in stunted children - Revi Gama Hatta Novika; Atriany Nilam Sari; Siti Nurhidayati; Rufidah Maulina; Luluk Fajria Maulida; Nurul Jannatul Wahidah; Muhana Fawwazy Ilyas; Lanjar Sumarno; Sigit Prastowo; Cecilia M. Jevitt (Annals of Pediatric Endocrinology & Metabolism, 2025)
Purpose Previous studies have suggested that milk consumption can promote growth in children. However, limited studies have been performed on the effects of cow milk varieties, especially β-casein A2 milk. This study aims to investigate the effect of β-casein A2 cow milk supplementation on physical growth, inflammation, and growth-related hormone and nutritional biomarker profiles in growth-stunted children. Methods This is a quasi-experimental study with only one group and a pre-and posttest design. This research is divided into 3 stages: allele testing in the β-casein gene, processing into ready-to-drink milk, and a clinical trial. The participants were children aged 12–36 months who were given 200-mL β-casein A2 cow milk supplementation once a day for 3 months. The outcome assessments were physical growth (body weight and height), inflammation (tumor necrosis factor-alpha [TNF-α] and cortisol levels), and biological markers related to growth and nutrition (insulin-like growth factor-1 [IGF-1], growth hormone [GH], and transferrin) that were measured during pre-, mid (week 6)-, and post (week 12)-intervention periods. Results This study included 30 study participants. Significant body weight and height improvements were observed at week 6 and postintervention (week 12) compared to preintervention. There were significant reductions in the inflammation markers TNF-α and cortisol levels postintervention. Additionally, IGF-1 and GH levels increased significantly, and transferrin levels also rose, potentially reflecting improved nutritional status. Conclusions This study suggests that β-casein A2 milk supplementation was associated with improvements in physical growth and related biomarkers in stunted children. Additionally, β-casein A2 milk may produce fewer BCM-7 metabolites compared to β-casein A1 milk, which has been hypothesized to be associated with certain adverse health outcomes. However, further controlled studies are needed to confirm its efficacy as a dietary intervention.